3D Organon VR Anatomy: A Virtual Anatomy Medical Education Tool. Issue 4 (2nd October 2021) - Weyant, Emily C.; Woodward, Nakia J.
Abstract: 3D Organon VR Anatomy is a virtual reality program that allows individuals to interact with anatomy in a 3D environment. This column provides a brief overview of the product and its potential uses within a medical library.